A novel ISLE-ESE method for mixed-variable experiment design. Issue 2 (January 2021) - Yang, J W; Wu, Z P; Wang, W J; Li, J X; Zhang, W H; Sun, J B; Zhao, H L; Wen, Q; Zhen, X
Abstract: Discrete-continuous mixed-variable problem is an inevitable problem in engineering design. However, few researches pay attention to discrete variables. In this paper, a novel method is proposed for solving mixed-variable problem by combing the Enhanced Stochastic Evolution (ESE) method and the improved Successive Local Enumeration (SLE) method. The continuous part of design variables is generated first. And then the improved SLE method is utilized to generate the discrete part. Finally, an overall optimization is conducted utilizing ESE method taking the continuous part of design variables as input. Results of numerical tests show that the proposed method performs better in both space-filling property and orthogonality. Besides, the computation effort is also saved compared to the ESE method.